VERSE (POETIC) EGO-DOCUMENTS IN MODERN OTTOMAN-TURKISH MILITARY HISTORY: FROM MILITARY MEMORY TO THE HISTORY OF EMOTIONS - Besikci, Mehmet (BURHAN CAGLAR, 2025)
This article examines verse (poetic) ego-documents of soldiers, a largely overlooked source type in modern Ottoman-Turkish military historiography, and argues for their recognition as distinctive historical texts, both in form and function. Focusing on examples from the late Ottoman wars and twentieth-century military memoirs, the study demonstrates that these narratives record military experience not only in factual terms but also through rich emotional expression. It highlights the continuity of these verse accounts with early modern Ottoman narrative traditions such as Ottoman military campaign narratives (gazavatname), memoir narratives (serguzestname), and the asik-style folk poetry. The article further contends that the poetic form-due to its flexibility in conveying emotions and its deep connection to oral culture-served as a powerful vehicle for transforming personal memory into collective remembrance. Accordingly, it positions verse autobiographies not merely as literary choices, but as meaningful records of the emotional dimensions of military life in the modern period. In doing so, the article suggests that these multilayered narratives offer fertile ground for integrating Ottoman-Turkish military historiography with newer approaches such as the history of emotions.
Keywords: Verse (poetic) Ego-documents; Military Memoirs; Ottoman Military History; History of Emotions; Military Campaign Narratives; Memoir Narratives; Asik-style Folk Poetry; History